2010
DOI: 10.3109/01913121003793067
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Varicocele Veins: Ultrastructural Study

Abstract: The authors believe this is the first report analyzing ultrastructual changes in normal human internal spermatic vein samples and in varicocele. The underlying molecular mechanisms of these changes await further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
4
0
10
Order By: Relevance
“…Of note, increased intimal and medial thickness in LEVVs and varicose spermatic veins, increased amounts of collagen fibers, and significantly decreased amounts of collagen fibers have been reported. [16][17][18] Some other studies also demonstrated that the amount of proteolytic enzymes and inflammatory mediators was increased in the varicose vein wall, resulting in endothelial dysfunction, increased wall permeability, and venous flow obstruction, ultimately leading to venous dilatation. [19][20][21][22][23] Furthermore, in a current study, it was shown that pelvic vein reflux contributed venous reflux into leg varicose veins, testicular veins, and hemorrhoidal veins in males.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, increased intimal and medial thickness in LEVVs and varicose spermatic veins, increased amounts of collagen fibers, and significantly decreased amounts of collagen fibers have been reported. [16][17][18] Some other studies also demonstrated that the amount of proteolytic enzymes and inflammatory mediators was increased in the varicose vein wall, resulting in endothelial dysfunction, increased wall permeability, and venous flow obstruction, ultimately leading to venous dilatation. [19][20][21][22][23] Furthermore, in a current study, it was shown that pelvic vein reflux contributed venous reflux into leg varicose veins, testicular veins, and hemorrhoidal veins in males.…”
Section: Discussionmentioning
confidence: 99%
“…Varicocele veins showed narrowing/obliteration of their lumens, destruction of the endothelial cells, invagination of the intima, and deposition of collagen bundles in the media layer. Ultrastructural changes included elongation of the endothelial cells with features of cellular damage, loss of the internal elastic lamina, and the appearance of ghost bodies and degenerative vacuoles in the subendothelial layer [22]. …”
Section: Physiopathology: Novel Conceptsmentioning
confidence: 99%
“…Những quan điểm trên chỉ đúng trong một số trường hợp nhất định mà không hoàn toàn giải thích được quá trình tiến triển và thay đổi của tĩnh mạch tinh giãn. Sự phát triển của kĩ thuật hiện đại cho phép quan sát, và phân tích cấu trúc vi thể của tĩnh mạch tinh giãn, từ đó làm sáng tỏ cơ chế bệnh sinh của bệnh [5], [6]. Thay đổi cấu trúc tĩnh mạch tinh giãn có thể quan sát được ngày dưới tiêu bản nhuộm Hematoxylin & Eosin (HE) bằng kính hiển vi quang học.…”
Section: đặT Vấn đềunclassified
“…Thay đổi cấu trúc tĩnh mạch tinh giãn có thể quan sát được ngày dưới tiêu bản nhuộm Hematoxylin & Eosin (HE) bằng kính hiển vi quang học. Theo đó quá trình biến đổi từng bước cấu trúc của thành tĩnh mạch từ thoái hóa cơ trơn đến xơ hóa toàn bộ đã được quan sát trên bệnh nhân giãn tĩnh mạch tinh trái độ III [6]. Quá trình biến đổi trên làm tăng kích thước thành mạch và giảm đường kính lòng mạch có thể ảnh hưởng đến lượng máu tuần hoàn tại tinh hoàn [7].…”
Section: đặT Vấn đềunclassified
See 1 more Smart Citation